Effects of gp120 Inner Domain (ID2) Immunogen Doses on Elicitation of Anti-HIV-1 Functional Fc-Effector Response to C1/C2 (Cluster A) Epitopes in Mice - Sherburn, Rebekah (Microorganisms, 2020)
Fc-mediated effector functions of antibodies, including antibody-dependent cytotoxicity (ADCC), have been shown to contribute to vaccine-induced protection from HIV-1 infection, especially those directed against non-neutralizing, CD4 inducible (CD4i) epitopes within the gp120 constant 1 and 2 regions (C1/C2 or Cluster A epitopes). However, recent passive immunization studies have not been able to definitively confirm roles for these antibodies in HIV-1 prevention mostly due to the complications of cross-species Fc–FcR interactions and suboptimal dosing strategies. Here, we use our stabilized gp120 Inner domain (ID2) immunogen that displays the Cluster A epitopes within a minimal structural unit of HIV-1 Env to investigate an immunization protocol that induces a fine-tuned antibody repertoire capable of an effective Fc-effector response. This includes the generation of isotypes and the enhanced antibody specificity known to be vital for maximal Fc-effector activities, while minimizing the induction of isotypes know to be detrimental for these functions. Although our studies were done in in BALB/c mice we conclude that when optimally titrated for the species of interest, ID2 with GLA-SE adjuvant will elicit high titers of antibodies targeting the Cluster A region with potent Fc-mediated effector functions, making it a valuable immunogen candidate for testing an exclusive role of non-neutralizing antibody response in HIV-1 protection in vaccine settings.